Pengaruh Profesionalisme dan Komitmen Organisasi Terhadap Kinerja Badan Pengawas LPD di Kecamatan Tabanan - Yuliana Pratiwi, Luh Kadek Nia; Kusumawati, Ni Putu Ayu (Hita Akuntansi dan Keuangan, 2025)
This research seeks to examine how professionalism and organizational commitment impact the performance of the LPD supervisory board in Tabanan District. The research focuses on LPDs within Tabanan District as the subject. The study's population consists of 36 LPD supervisory bodies in Tabanan District. The findings indicate that professionalism plays a significant role in influencing the performance of the supervisory board in Tabanan District's LPDs. Professionalism encompasses the ability to proficiently understand both the technical and theoretical aspects of their field and the skills relevant to their roles as examiners. Furthermore, organizational commitment has a direct influence on the performance of the LPD supervisory board in Tabanan District. A higher level of commitment among LPD supervisors in Tabanan District corresponds to an improved performance of the supervisory board.